ANALISIS HARGA SAHAM PADA PERUSAHAAN ASURANSI YANG GO PUBLIK DI BURSA EFEK INDONESIA PERIODE 2005 – 2009 - Amarullah, Sri Marniyati; Hadi, Syamsul (Jurnal Ekonomi Pembangunan, 2011)
The purpose of this study was to measure the influence of Price Earning Ratio (PER), Leverage Ratio (LR), Return On Equity (ROE), Price to Book Value (PBV) on Stock price in the insurance company. The analysis used the quantitative analysis of multiple linear regression model using ordinary least squares (OLS). From the results, it could be explain that the variables price earning ratio, leverage ratio, return on equity and price to book value has a significant influence on Stock price together was amounted to F calculated 3,896 > F table 2,61. From the t test, each variables that significantly influence the Stock price were PER (2,108 t calculate > t-table 2,021), ROE (2,654 t calculated > t-table 2,021. On the contrary,  the variables that were not impact significantly were LR (1,318 t calculated < t-table 2,021) and PBV (-3,141 t calculated > t-table -2,021). Based on these results, obtained empirical evidence that could be considerated towards a more in-depth study on Stock price. It would be interesting if further study pay attention to the technical factors as well as policies set by the government.